2020
DOI: 10.1109/access.2020.3020623
|View full text |Cite
|
Sign up to set email alerts
|

Towards an Adaptive Design of Quality, Productivity and Economic Aspects When Machining AISI 4340 Steel With Wiper Inserts

Abstract: The continuous pursue of sustainable manufacturing is motivating the utilization of new advanced technology, especially for hard to cut materials. In this study, an adaptive approach for optimization of machining process of AISI 4340 using wiper inserts is proposed. This approach is based on advance yet intuitive modeling and optimization techniques. The approach is based on Artificial Neural Network (ANN), Multi-Objective Genetic Algorithm (MOGA), as well as Linear Programming Techniques for Multidimensional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…The optimal results of MOGA and MOPSA are significantly close, while MOEPCA shows the best optimal results for the MRR but with a slightly higher surface roughness, which is undesirable. However, the obtained results, compared to [31], show moderate levels of cutting speed, low feed rates and higher depths of cut based on the selected parameter levels. Despite the similar results obtained from MOGA, MOPSA and MOEPCA of the wiper model, MOPSA outperformed the other two algorithms in computational time, as it was 30 times faster than MOGA and 20 times faster than MOEPCA.…”
Section: Optimization Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…The optimal results of MOGA and MOPSA are significantly close, while MOEPCA shows the best optimal results for the MRR but with a slightly higher surface roughness, which is undesirable. However, the obtained results, compared to [31], show moderate levels of cutting speed, low feed rates and higher depths of cut based on the selected parameter levels. Despite the similar results obtained from MOGA, MOPSA and MOEPCA of the wiper model, MOPSA outperformed the other two algorithms in computational time, as it was 30 times faster than MOGA and 20 times faster than MOEPCA.…”
Section: Optimization Resultsmentioning
confidence: 80%
“…The obtained cutting parameters considering the minimum surface roughness were a cutting speed of 155 m/min, a feed rate of 0.12 mm/rev and a depth of cut of 0.8 mm [ 30 ]. Furthermore, an adaptive approach was presented in which a multi-objective genetic algorithm was modified using linear techniques for multidimensional analysis of preference (LINMAP) [ 31 ]. The experimental work was carried out based on higher cutting speeds of up to 200 m/min using two different cutting inserts: wiper and conventional inserts.…”
Section: Introductionmentioning
confidence: 99%
“…Similar research was conducted using Wiper coated carbide insert by Kurniawan et al [19]. Abbas highlighted that using Wiper insert not only leads to superior surface integrity compared to conventional ones but also higher productivity can be achieved [20]. Nevertheless, it should be stated that hardness of materials has a significant impact for the tool life [21].…”
Section: Manufacturers Of Cutting Tools Do Not Providementioning
confidence: 78%
“…Researchers have reported that wiper inserts showed an excellent performance in terms of the surface quality at higher rates of feed compared to conventional inserts, though the process parameters [ 44 ] and cutting tool geometry [ 32 ] did affect the surface quality when using a wiper insert for hard turning. Although using wiper inserts enhanced the surface quality and increased productivity [ 35 ], it also showed higher tool rake wear, cutting force, and temperature compared with conventional inserts [ 17 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, conventional inserts showed higher flank wear compared with the wiper inserts [ 13 , 31 ]. In addition, a recent work offered an adaptive design model to achieve a balance between the cost, productivity, and quality aspects when using wiper inserts [ 44 ].…”
Section: Introductionmentioning
confidence: 99%